Architecture-Independent Programming for Wireless Sensor Networks : an Architecture-Independent Approach. - Bakshi, Amol B., 1975- (John Wiley & Sons, 2008)
New automated, application-independent methodology for designing and deploying sensor networks. Following this book's clear explanations, examples, and illustrations, domain experts can design and deploy nontrivial networked sensing applications without much knowledge of the low-level networking aspects of deployment. This new approach is based on the Abstract Task Graph (ATaG), a data-driven programming model and an innovative methodology forarchitecture-independent programming and automatic software synthesis for sensor networks. ATaG programs are concise, understandable, and network-indepen.